Exploration of Physics Concepts in Milkfish Cultivation as An Ethnoscience Study in Sidoarjo - Nina Fajriyah Citra; Nadi Suprapto; Setyo Admoko (Universitas Lambung Mangkurat, 2022)
Indonesia has a cultural diversity embedded in the local wisdom of the region and has become an invaluable asset. Local wisdom is a form of native science of the community that has not been conceptualized scientifically but still can be a potential source of learning for students to study science as a form of ethnoscience. One of the local wisdom in Sidoarjo Regency is the milkfish, a city icon. This research aims to explore the concept of physics in milkfish cultivation. It can be developed to be applied in science learning in schools. This study is a qualitative descriptive study using observation methods and interviews directly with pond workers. In addition, researchers also conduct literature studies to strengthen the analysis of the data obtained. According to the findings, physical concepts are contained in the management system of milkfish ponds, including measurement materials, static fluids, dynamic fluids, thermodynamics, optics, and relativity.